PENGEMBANGAN MEDIA ULAR TANGGA NUMERASI (ULTRASI) BERBASIS CANVA UNTUK MENINGKATKAN HASIL BELAJAR DI UPT SD NEGERI DOROMUKTI - Anandifa, Fetty Nabila; Wendri Wiratsiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The main objective of this study is to develop a canva-based snake and ladder numeracy learning media (ultrasi) to improve the learning outcomes of elementary school students, especially in mathematics. This study applies the research and development method (R&D) through the ADDIE development model. The target is class V of UPT SD Negeri Doromukti. Initial data was obtained through pre-test results which showed that only 38.88% or 7 students scored above the Minimum Completion Criteria (KKTP), while 61.11% of other students were still below the KKTP. The canva-based snake and ladder numeracy media (ultrasi) developed by the researcher was validated by 3 validators, with validation results, namely: media experts 92%, material experts 94%, and language experts 98%. Meanwhile, the effectiveness test of the canva-based snake and ladder numeracy media (ultrasi) was measured using the N-Gain formula and experienced an increase of 60% which is included in the fairly effective category. In addition, the results of the practicality test through a questionnaire showed that the canva-based snake and ladder numeracy (ultrasi) media is very feasible to be implemented in the learning process, with the results of the teacher response percentage value of 95.5% and the student response of 96.6%. Based on the results of the percentage, the canva-based snake and ladder numeracy (ultrasi) media can be declared feasible, effective, and practical to be used as an alternative learning media in improving the learning outcomes of Elementary School (SD) students.